Asymmetric azide-alkyne Huisgen cycloaddition on chiral metal surfaces - Samuel Stolz (Nature Portfolio, 2021)
Mechanistic insight into enantioselective reactions at intrinsically chiral surfaces can be challenging to obtain. Here the catalytic activity of Pd1- and Pd3-terminated PdGa{111} surfaces is shown to differ substantially, with Pd1-terminated surfaces promoting on-surface azide– alkyne cycloadditions enantioand regioselectively.